Acute chemical skin injuries in the United States: a review. (9th August 2018) - Hall, Alan H.; Mathieu, Laurence; Maibach, Howard I.
Abstract: The objective was to perform a thorough review of published and other available data to elucidate the extent of chemical skin injuries in the US. Chemical skin injuries differ significantly from skin lesions produced by other injury mechanisms, so this review was restricted to the former. Retrieval of relevant published data was performed in PubMed and Google. Other data were retrieved from the American College of Surgeons National Trauma Databank, American Burn Association National Burn Repository, US Department of Labor Bureau of Labor Statistics, websites of all 50 US States Departments of Health, and the National Poison Data System of the American Association of Poison Control Centers. Two areas of significance in disfiguring skin burn injuries and particularly of chemical skin injuries, psychosocial issues and the associated financial burden, have been briefly reviewed. Because of the paucity of published data, international as well as US data have been included. A brief description of an active flushing fluid as an alternative to potable water, Diphoterine ® solution, has also been included. Chemical skin injuries generally comprise approximately 2–5% of all skin burns, but sometimes higher percentages have been reported. Data analysis shows that while there are various sources regarding the epidemiology of chemical skin injuries, the total annual number cannot be determined because there is no centralized US national reporting mechanism. Literature and clinical experience demonstrate the importance of chemical skin injuries in USA. Dermal exposures to chemicals can result in mortality and morbidity. Chemical skin injuries can be avoided or ameliorated and preventive advanced measures should be taken to reduce or ameliorate them.